Mathematical Characterization of Inorganic Salt Precipitation From the Reaction of CO2 With Formation Brine and Its Application - Yuan, Zhou; Liao, Xinwei; Zhang, Kuaile; Zhao, Xiaoliang; Chu, Hongyang; Zou, Jiandong (Frontiers in Energy Research, 2020)
In the process of CO2 enhanced oil recovery (CO2-EOR), CO2interacts with formation brine containing high concentrations of scale-forming ions to produce inorganic salt precipitation, which blocks the rock pore throats, changes the characteristics of the reservoir and thereby reduces the oil recovery rate. In this study, a series of experiments on the static reaction of CO2-formation brine were conducted. The amounts of precipitation formed from the interaction of CO2-formation brine under various conditions were tested. Using the PHREEQC software, the mathematical characterisation formulas between the precipitation amount and various environmental factors (e.g. temperature, pressure difference, scale-forming ion concentration and pH) were established. On this basis, a numerical simulation model of CO2 flooding in a typical area of Oilfield C was established. The distribution of inorganic salt precipitation during continuous gas flooding was predicted, and the effect of inorganic salt precipitation on oilfield recovery was analysed.